PENGHINDARAN PAJAK, TUNNELING, KONEKSI POLITIK, DAN NILAI PERUSAHAAN NON KEUANGAN INDONESIA - Rahmadita, Aulia (UNIB Press, 2019)
This study aims to provide an empirical evidence of about is the effect of tax avoidance on tunneling, tunneling moderate tax avoidance on firm value and political connection to moderate the effect of tax avoidance on firm value. The population in this study are all non-financial companies listed in Indonesia Stock Exchange 2012-2016. The sample of this research is 86 non-financial sector companies listed on Indonesia Stock Exchange 2012-2016. collection method using purposive sampling technique. were selected as a sample of the total 286 observations this study. The method of analysis in this study using regression analysis two stage last square.The results of this study indicate that: 1) Tax Avoidance has positive and significant effect on tunneling using OREC and NOREC1 proxies. 2) tunneling that moderates tax avoidance does not affect the firm value. 3) political connection that moderates tax avoidance does not affect the firm value.